Complicaciones asociadas a la inserción de catéteres percutáneos en la unidad de cuidados intensivos de neonatología - García Macancela, Doris Janneth (2025)
In the neonatal intensive care unit, newborns in critical condition who require specialized management are cared for, making it necessary to obtain central venous access; the peripherally inserted catheter is considered the most appropriate. The article aimed to determine the main complications associated with the insertion of percutaneous catheters in the neonatology area of the Vicente Corral Moscoso Hospital during the period January - June 2024. It was a quantitative and descriptive study. The population was represented by 650 newborns, 84 of whom made up the sample. The most prevalent gender was female (56.0%), a monolumen catheter was used (51.2%), the cephalic route was the most used (47.6%), at the time of catheter insertion there was a complication in 35.7% of cases, being necessary between 1 - 2 attempts (65.5%), the duration was ≥15 days (65.5%). The reasons for implant removal were discharge (38.1%), catheter complications (29.8%) and death (16.7%). The most commonly observed complications were leakage, edema and fracture or rupture of the catheter. There is a statistically significant relationship between the duration of the catheter and the presence of complications. However, in this series no relationship was verified between the appearance of complications and the sex of the neonate, the type of catheter used, the insertion site, the occurrence of complications during placement, or the number of attempts that were necessary to achieve successful catheter insertion. KEY WORDS: percutaneous catheter, neonate, neonatology, intensive care unit.